Calculation of Radiation and Matter Dominant Universe by Applying the Power Law Inflation (Journal of Bangladesh Academy of Sciences, 2010)
The homogeneous and isotropic Brans-Dicke cosmological solutions satisfying Whitrow-Randall's relation which have been discussed by Bermann and Som were examined. After correcting an error in their work, we extended and examined their results obtaining the radiation and matter dominant universe applying the power law. DOI: 10.3329/jbas.v33i2.4105 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 219-226, 2009